Early Childhood Education Teachers’ Readiness in Implementing the Disaster Safe School Guidelines for Disaster Mitigation Education Related to Mount Merapi Eruptions - Af'idah, Nabila Zakiyyatul; Waluyo, Edi; Setiawan, Deni (AL-ISHLAH: Jurnal Pendidikan, 2026)
Early Childhood Education (ECE) institutions in disaster-prone areas face critical challenges in implementing the Disaster Safe School Guidelines (Satuan Pendidikan Aman Bencana/SPAB). While disaster education has been widely studied at primary and secondary levels, limited research explores teacher readiness in ECE contexts, particularly in high-risk volcanic regions such as Mount Merapi.This study employed a qualitative descriptive design to examine ECE teachers’ readiness in implementing SPAB guidelines. Data were collected through in-depth interviews, observations, and document analysis involving six teachers and two principals from two ECE institutions located in high-risk zones. Data were analyzed using Miles and Huberman’s interactive model, including data condensation, display, and verification, supported by thematic coding.The findings indicate that teacher readiness is a multidimensional construct shaped by the interaction between individual competence, institutional capacity, and socio-cultural context. Teachers demonstrated strong affective commitment and pedagogical creativity in integrating disaster education through play-based learning. However, their conceptual and technical understanding of SPAB remained fragmented due to limited formal training and weak policy support. Institutional readiness varied, influenced by leadership, infrastructure, and community engagement. Key barriers included insufficient resources, lack of structured training, and absence of formalized policies.This study conceptualizes teacher readiness as an ecosystem-based construct, emphasizing the dynamic interplay between experience, institutional systems, and community support. Strengthening SPAB implementation requires integrated efforts through continuous professional development, policy alignment, and cross-sector collaboration.